Design and Implementation of Visible Spectrophotometer Virtual Instrument Based on LabVIEW 8.0 - Li, Jiangyuan; Guo, Depeng; Meng, Hu (Asian Journal of Chemistry, 2010)
A chemical virtual instrument system of visible spectrophotometer is developed based on LabVIEW 8.0 with 723A spectrophotometer. This system completed automatic data collection, saving, display momentarily, results generation, etc. It not only avoids the tedious manual work, data processing and man-made error, but also improves the efficiency and veracity of determination. Experiment says that LabVIEW, as a virtual programming language, has a unique advantage in the development of virtual instruments, such as the compendious method of graphical programming approach and the special function in LabVIEW program. This virtual instrument is applied to evaluate the iron, chromium and phosphorus contents in feed.